Antagonisme Sosial, Diskonsensus, dan Rantai Ekuivalensi: Menegaskan Kembali Urgensi Model Demokrasi Agonistik - Hanif, Hasrul (Jurnal Ilmu Sosial dan Ilmu Politik, 2007)
Debates on linkages between democracy and welfare remain fascinating issues in contemporary democracy studies, especially in Indonesia. Howeuer, mainstream studies on such issues were influenced, foremost, by political economy approaches and classic liberalism. Thus, mainstream studies pay less attentions on decontruct both the idea of democrary and welfare and tend to essensialize democracy and welfare. lt also insulate politics from conflict and social antagonisms. Rather than analysing pattern of linkages betwoeen welfare and democracy, this study inquire about welfare itself âas common goodsâ is empty/floating signifier and then put emphasis on welfare âas articulatory social practices and discursiae realityâ always been produced, presented and represented in and through political process or battle for hegemony. Moreover, whilst this study underline the primacy of political and discursive social practices, it strongly differ from model of deliberative democracy (liberal pluralist) since it re-emphasize agonistic model of democracy, that was introduced by post-marxist or radical pluralist thinkers. Last of all, agonistic model of democracy deem conflict, undecidability and social antagonism as virtue of democracy and main of political life.